Baalbek, Libanon. Die Arbeiten des Jahres 2019 - Van Ess, Margarete; Nádor, Julia; Wienholz, Holger (e-Forschungsberichte des DAI, 2020)
Field research in Baalbek, located in the northern Beqaa plain of Lebanon, was resumed in summer 2019. Investigations took place in three areas and scholarly topics: small soundings in an area with medieval and late antique architectural remains should evaluate the scientific potential. In the famous Jupiter sanctuary, systematic investigation was also carried out into the use of colours in the buildings. In addition, the excavations in the pre-Roman mound under the altar courtyard of the Jupiter sanctuary were resumed and Middle Bronze Age strata investigated. The planing for the conservation and presentation of the ruins were also continued. Projects for the presentation of the monumental Roman bath are currently being developed.